Effectiveness of food subsidies in raising healthy food consumption: Public distribution of pulses in India - Chakrabarti, Suman; Kishore, Avinash; Roy, Devesh (International Food Policy Research Institute, 2016)
There is an increasing demand to add pulses to the basket of subsidized goods in the Public Distribution System (PDS) of India—the world’s largest food-based social safety-net program. Would subsidizing pulses through PDS lead to a significant increase in its consumption? We study the case of subsidy on pulses in select Indian states and its impact on consumption and ultimately nutrition (in terms of protein intake) by exploiting an exogenous variation in prices to answer this question. Between 2004/2005 and 2009/2010, four Indian states introduced subsidized pulses through the country’s PDS, while other states did not. We exploit exogenous price variations to examine whether the price subsidy on pulses achieves its goal of increasing pulse consumption, and by extension protein intake, among India’s poor. Using several rounds of consumption expenditure survey data and difference-in-difference estimation, we find that the change in consumption of pulses due to the PDS subsidy, though statistically significant, is of a small order, and not large enough to meet the goal of enhancing the nutrition of beneficiaries.